Is there any correlation between Estradiol supplementation, as luteal phase support, and clinical pregnancy in ART cycles? A cross-sectional study - Maryam Eftekhar; Banafsheh Mohammadi; Esmat Mangoli; Maryam Mortazavi (Shahid Sadoughi University of Medical Sciences, 2020)
Background: Endometrial receptivity is one of the important factors in assisted reproductive technology (ART) success. In the luteal phase of an ART cycle, serum estradiol (E2) and progesterone are often placed in low levels. Supporting the luteal phase with progesterone is a usual method. Objective: To evaluate the effects of E2 supplementation plus progesterone on the luteal phase support in the antagonist protocol who have undergone intracytoplasmic sperm injection-embryo transfer cycles. Materials and Methods: In this cross-sectional study, 200 patients with antagonist stimulation protocol, who had undergone intracytoplasmic sperm injection treatment, were divided into two groups based on the use of E2 supplementation. In both groups, 400 mg progesterone suppositories (CyclogestⓇ), twice a day/vaginally, was administered starting from the day of oocyte collection until the fetal heart activity. However, in the E2 group, in addition to progesterone, 4 mg tablet of E2 was received daily. Beta hCG was checked 14 days after the embryo transfer, and the clinical pregnancy rate was the main endpoint. Results: The patients' characteristics were matched, and insignificant differences were observed, except for endometrial thickness. The clinical outcomes showed the rate of pregnancy was higher in the E2 group compared to the control group; nonetheless, statistically, there was no noticeable difference. Conclusion: E2 supplementation had no beneficial effect in the luteal phase support of IVF cycles. Nevertheless, more studies are required to confirm the supportive role of E2 supplementation for embryo implantation and to improve the outcomes in ART cycles.